Estudo experimental e de simulação da dinâmica de material particulado em tambor rotatório com suspensores - Nascimento, Suellen Mendonça (2014)
Drying is a unit operation present in several industrial processes; one of the most widely used equipment for drying are flighted rotary dryers, which are cylindrical drums with flights in order to elevate the material and shower it over the cross section. Understanding the solids discharge profiles is extremely important to describe the behavior of particles in them. For this, usually are used rotating drums with flights without the presence of the drying air, to facilitate the measurement of particle dynamics in these processes. The computational fluid dynamics (CFD) is a very viable and increasingly used method that coupled with experimental work can provide excellent results. In the use of computational fluid dynamics, to simulate the dynamics of a particulate material in a rotating drum with flights, was used the Euler-Euler approach. In order to compare with the experimental results, was developed a method of image analysis that allows estimate the holdup on flights through the area of the mass fractions on the cross sections of the drum. Thus, the work aimed to study the influence of material type, particle diameter and rotation speed in the behavior of particles in a rotating drum with flights and the design load. Also, it was analyzed the influence of these variables for the dynamic friction coefficient for the glass beads and it was observed that the particle diameter influenced the dynamic friction coefficient and hence the particles discharge profile. The results of holdup in function of angular position were very important to verify the effects of the dynamic operating variables of the particles. Furthermore, in the CFD modeling, it was ranged the limits of frictional viscosity and it was possible to obtain values very close to the experimental one. According to the limit of frictional viscosity that was closest to the experimental results, in which it should be applied in any region of the drum, the results allowed an interpretation on the nature of the numerical solver (FLUENT ®), as well as the interpolations generated between one cell and another of the computational mesh.